PENGARUH PELATIHAN, REWARD DAN MOTIVASI TERHADAP KINERJA PENELITIAN DOSEN DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU - Rahmadianti Tri; Marnis Marnis; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study was aimed to examine the effect of training, reward, and motivation of the lecturer’s research. This research was conducted at The Faculty of Economic and Business Riau University. Primary data was collected by questionnaires to 74 lecturers as a sample. Secondary data comes from the literature related to this study. To test the hypothesis in this research is using Multiple linear regression analysis with Statistical Program for Social Sciences (SPSS). The result showed that 1) Training has a positive and significant effect on the performance of lecturer’s research 2) Reward does not have a positive and significant effect on the performance of lecturer’s research, 3) Motivation had a positive and not significant effect on the performance of lecturer’s research 4) Training, Reward and Motivation has a significant effect on the performance of lecturer’s research.Keyword: Perfomance, Motivation, Training, Reward